Hubungan umur dan menopause dengan kejadian prolapsus uteri di RSUD Panembahan Senopati - Heni Suryani; Suherni Suherni; Yani Widyastuti (Jurnal Kesehatan Ibu dan Anak, 2013)
Data Haalth office Yogyakarta showing two consecutive years (2oog-2010) there was an increase in the incidence of uterine prolapse Bantul 15.1%. The causes are common in uterine prolapse is the age and menopause. ln old age and menopause, estrogen has been reduced so that the pelvic floor muscles lo atrophy and weaken. Morbidity due to uterine prolapse is defecation, urination and sexual function. Based on preliminary studies in hospitals Panembahan Senopati obtained 128 patients experienced uterine prolapse in 2011. Objective: to knowing the relationships maternal age and menopausal status with the incidence of uterine prolapse in Panembahan Senopati Hospital in 2o11. Methods this study is an observational analytic cross-sectional approach. The samples were all gynecological patients in Poly Gynecology Hospital Panembahan Senopati who meet the inclusion and exclusion criteria totaling 196 subjects. Using the format of the data collection instrument records obtained from medical records. Further univariate analysis, the chi-square bivariate and multivariate logistic regression analysis. Results the proportion of study subjects aged > 55 years was 55.1% and age <55 years 44.9%. The results of the bivariate correlation p-value O.OOO, Rp = B.305 and multivariate correlation results p = 1.760, Cl (2.484 to 13.610). The proportion of subjects who menopause 56.1%, 43.9% were not menopausal. The results of the bivariate correlation p-value 0.000, RP = 6.624, multivariate correlation results p = 1..412, Cl (1.9O4 to 9.984). There is a significant relationship between age and the menopause the incidence of uterine prolapse. the variable age has a greater influence on the occurrence of uterine prolapse than menopause variables.